Категорія "правова традиція українського народу" у дискурсивному пізнанні сучасної правової системи - Лобода, Ю. П.; Loboda, Ju. (My University, 2009)
The article deals with the author's interpretation of the category of law. The significance of ethnography in the process of law tradition cognition is pointed out. During the investigation, the main contradictions of modern law system of the ukranian people are figured out.
Лобода Ю. П. Категорія "правова традиція українського народу" у дискурсивному пізнанні сучасної правової системи / Ю. П. Лобода // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 90-100.
Keywords: правова традиція; етнографія; методологія юридичної науки; правова система України; правовая традиция; этнография; методология юридической науки; правовая система Украины; egal tradition; ethnography; methodology of jurisprudence; Ukrainian legal system